Internalisasi Nilai-Nilai Sosial dalam Pembelajaran Pendidikan Agama Islam Sebagai Strategi Pembentukan Karakter Humanis di Era 5.0 - Dwi Adhi Widodo; Syaiful Hadi; Misbahun Nidhom (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Lhokseumawe, 2025)
The emergence of Society 5.0 represents a paradigm shift that integrates technology deeply into daily life while posing challenges such as social character degradation and digital individualism. This study qualitatively examines the strategic role of Islamic Religious Education (PAI) in fostering humanistic character and spirituality among learners in response to these changes. Through systematic literature review with descriptive-analytical design, findings reveal that digital-humanistic pedagogy, which positively integrates technology with ethical values, effectively internalizes social values in PAI. The implementation of blended learning and the